KEDUDUKAN HAK ULAYAT DALAM HUKUM TANAH NASIONAL (UUPA) DI INDONESIA - Masitahpohan Masitah pohan (jurnal.unprimdn.ac.id, 2019)
Customary land rights as a form or method of ownership of land by legal institutions are widely available in the archipelago, and even constitute the largest number of land areas in Indonesia. Customary communal land is a form of customary community's legal territory whose ownership is controlled by a group of tribes who inhabit a certain area under the leadership of a traditional shop or tuaka. The formal legality of customary rights of indigenous peoples has a place in the national land law (UUPA), but in the level of law in action there is still lack of legal protection when dealing with development interests, so as to make the community that owns customary rights become marginalized. Which results in structural impoverishment.